2011
DOI: 10.1002/app.34237
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric barrier discharge plasma induced surface modification of polyester/cotton blended fabrics to impart water repellency using HMDSO

Abstract: Continuous treatment of polyester/cotton blended fabric samples was carried with hexamethyldisiloxane (HMDSO) plasma on the pilot scale atmospheric pressure plasma reactor. The mixture of helium and argon was used as carrier gas for generating dielectric barrier discharge plasma. The effect of discharge power and treatment time on the water repellent properties of samples were evaluated with contact angle (CA) and spray test measurements. Spray test and CA results showed improved resistance to wetting with wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…assigned to asymmetric stretching of aromatic ester, 710 cm −1 attributed to aromatic C-H bending vibrations and 871 cm −1 attributed to C-C out of plane bending vibrations of the benzene rings ( Figure 1-a) [19]. At the same time the spectra also displays the very strong bands at 1160, 1100 and 1020 cm -1 assigned to the vibrations of the C-O-C bond of the glycoside bridges of the cellulose structure [20].…”
Section: Resultsmentioning
confidence: 99%
“…assigned to asymmetric stretching of aromatic ester, 710 cm −1 attributed to aromatic C-H bending vibrations and 871 cm −1 attributed to C-C out of plane bending vibrations of the benzene rings ( Figure 1-a) [19]. At the same time the spectra also displays the very strong bands at 1160, 1100 and 1020 cm -1 assigned to the vibrations of the C-O-C bond of the glycoside bridges of the cellulose structure [20].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it led to a decrease in desired groups. Many studies showed the effect of plasma polymerization power on the contact angle of the resulting coating [85,86].…”
Section: Ii-4-2-influence Of Input Power On Wettabilitymentioning
confidence: 99%
“…Their favorable properties, such as their low gas temperature nature and easy operation, have allowed them to play an essential position in many areas, including in surface cleaning, etching, surface modification, film deposition, sterilization, etc. [1,2]. Thermally sensitive polymeric material surface modification is an active area of atmospheric pressure plasma research because the academic/industrial field urgently needs an effective and simple method to tailor polymer surface properties.…”
Section: Introductionmentioning
confidence: 99%